Flunked - Calonita, Jen (Calonita, Jen. Fairy Tale Reform School., 2015)
When petty thief Gilly, who lives with five younger brothers and sisters in a run-down boot, gets caught stealing, she is sentenced to three months at Fairy Tale Reform School, where all of the teachers are former villains, including the Big Bad Wolf, the Evil Queen, and Cinderella's Wicked Stepmother.